Evaluation of Multiplex PCR System for Simultaneous Detection of Escherichia coli O157:H7, Listeria monocytogenes and Salmonella enteritidis in Shrimp Samples - Yasmin, Mahmuda; Kawasaki, Susumu; Kawamoto, Shinichi (Bangladesh Journal of Microbiology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> A multiplex polymerase chain reaction (PCR) method was evaluated for simultaneous detection of Escherichia coli O157:H7, Listeria monocytogenes and Salmonella enteritidis in shrimp samples. The sensitivity of DNA amplification by PCR in this method was found to be 103 cfu/ml for each pathogen. When this protocol was adopted for the detection of each of the above mentioned pathogen in spiked shrimp extract culture, similar sensitivity was observed. However, this method detected 1 bacterial cell for E. coli O157:H7 and S. enteritidis and 100 for L. monocytogenes per 25 g spiked shrimp samples after overnight enrichment. In the commercially imported shrimp samples, none was found to contain any of the three pathogens by multiplex PCR or by conventional method, which suggests that the multiplex PCR is a reliable and useful for rapid screening of shrimp samples for E. coli O157:H7, L. monocytogenes and S. enteritidis. This will save time and increase our ability to assure food safety. Keywords: Multiples PCR, Shrimp extract, Spiked sample, Escherichia coli O157:H7, Listeria monocytogenes, Salmonella enteritidis DOI: http://dx.doi.org/10.3329/bjm.v24i1.1236 Bangladesh J Microbiol, Volume 24, Number 1, June 2007, pp 42-46